Rapid quantification of cellular proliferation and migration using ImageJ. (12th February 2019) - Venter, C; Niesler, CU
Cellular proliferation and migration are crucial during development, regeneration and disease. Methods to quantify these processes are available; however, many are time consuming and require specialized equipment and costly reagents. Simple cell counts (proliferation analysis) and the scratch assay (migration analysis) are favorable methods due to their simplicity and cost–effectiveness; however, they rely on subjective and labor-intensive manual analysis, resulting in low throughput. We have developed optimized protocols to rapidly and accurately quantify adherent cell number and wound area using ImageJ, an open-source image processing program. Notably, these adaptable protocols facilitate quantification with significantly greater accuracy than manual identification.